Population growth and urban development in Al-Salt city - Wishah, Mohammad Wishah AbedelKareem (Journal of Humanities & Social Sciences, 2020)
The research aimed to study the phenomenon of population growth and its impact on urban development in the city of Salt, through studying the relationship between them, and the research followed the historical and analytical approach. The research reached a number of results, the most important of which is the existence of a great relationship between population growth and urban growth in the various governorates and regions, as population growth leads to an increase in the size of urban centres. The results of the 2015 census showed that the total population in the city of Salt was (99,890) people; of whom (52095) were males, i.e. (52.1%), and (47,795) were female (47.9%), and the gender ratio reached (108) Male to every hundred females; this percentage corresponds to the global proportion. Moreover, the results showed that the Jordanian and non- Jordanian community residing in the city of Salt is a young community, as the number of people between the ages of (15- 64) years reached about (66214) people with (66.3%) of the population As- Salt city. As well as, the Salt city has expanded as a result of the increase in the population, its area increased from (3.2 km2 in 1952) to (35.99 km2 in 1994), and it reached to (80 km2 in 2015). Furthermore, there is only one Hospital at a Salt, King Hussein Hospital, and serves more than (156260). Finally, the number of government schools in the city of Salt has reached 43 schools in 2015 distributed over the different neighbourhoods of the city.
Keywords: population growth; urban development; the city of Salt